E-Test or Agar Dilution for Metronidazole Susceptibility Testing of Helicobacter pylori: Importance of the Prevalence of Metronidazole Resistance - Chen, Jinnan; Huang, Yu; Ding, Zhaohui; Liang, Xiao; Lu, Hong (Frontiers in Microbiology, 2022)
Background A number of studies have shown that E-test overestimated the presence of Helicobacter pylori resistance compared to agar dilution. Objective The purpose of this study was to explore whether E-test could be an alternative for agar dilution to detect the metronidazole susceptibility of H. pylori. Method E-test and agar dilution were used to assess the susceptibility of H. pylori to metronidazole, clarithromycin, and levofloxacin in 281 clinical isolates obtained from China where the resistance was high. Cohen’s kappa analysis, McNemar’s test, and essential and categorical agreement analysis were performed for these two methods. Results Overall, the result of the E-test showed a similar prevalence of resistance rate to all antibiotics compared with agar dilution. The essential agreement of the E-test method and agar dilution in the evaluation susceptibility of H. pylori to clarithromycin and levofloxacin was moderate at 89.0 and 79.7%, respectively, but only 45.9% for metronidazole. The results shown by a categorical agreement (CA) between the E-test and agar dilution were 100% for both clarithromycin and levofloxacin. As for metronidazole, the CA was 98.7%, no major error was identified, and the rate of a very major error was 1.8%. Conclusion E-test can be an alternative method to detect the metronidazole susceptibility of H. pylori.